Altered molecular metabolism of knee joint tissues in a botox induced quadriceps muscle weakness model in the rabbit. Issue 4 (27th March 2011) - Leumann, A; Fortuna, R; Longino, D; Leonard, T; Hart, D; Valderrabano, V; Herzog, W
Abstract : Background: Muscle weakness due to joint injuries (eg, anterior cruciate ligament rupture) or muscle injuries (eg, muscle strain) are very frequent in sports. Objective: To analyze changes to knee joint ligaments and menisci induced by quadriceps muscle weakness by measuring molecular metabolism. Design: Prospective randomised controlled trial. Setting: Laboratory study. Interventions: Chronic quadriceps muscle weakness was induced in six 1-year old New Zealand White rabbits through monthly injections of Botox (botulinum toxin A) for six months. Five age- and sex-matched rabbits served as controls. Main outcome measurements: Muscle weakness was assessed by measuring muscle weight, isometric quadriceps force, and histologic muscle degeneration. Molecular metabolism was measured in the patellar tendon, medial and lateral collateral ligaments, and medial and lateral menisci by measuring total RNA yields, and nine tissue specific RNA yields (eg, Collagen I, MMP-III). Results: Muscle weights were decreased by 46.6%, muscle forces by 58.6 to 61.3% depending on the knee flexion angle, and cross sectional areas of the contractile apparatus by 54.7% (all results p<0.001) for the test—compared to the control group animals. Molecular analysis showed significantly decreased overall turnover (MMP-I), and significantly decreased metabolism for anabolic factors (Collagen I, MMP-III, MMP-XIII, TGFâ) and reduced injury response (Collagen III, MMP-XIII). Discussion: Quadriceps muscle weakness leads to adaptive changes in knee joint structures by adjusting specific RNA activities while overall cell metabolism remains unchanged. In the concept of the joint as an organ, this may reflect a new functional steady-state. Muscular unloading of the knee might impair the biomechanical function of the knee joint and its component structures. This could describe an underlying pathomechanism of the fact, that injured athletes are more susceptible to additional overuse injuries than healthy athletes. Therefore, we suggest that weaknesses of muscles and component joint structures being considered in injury treatment and rehabilitation.